Diaspores biometry, temperatures and light regime on seed germination of Ptychosperma macarthurii (Arecaceae) - De Souza, Antonio Maricélio Borges [UNESP]; Ferreira, Kássia Barros [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP]; Ferraz, Marcos Vieira [UNESP] (Lepidus Tecnologia, 2022)
This work aimed to analyze diaspores biometric characteristics, the effect of different temperatures and light regimes on seed germination, and the initial seedlings' growth of Ptychosperma macarthurii. The experiment was carried out at the Laboratory of Horticultural Seeds at São Paulo State University (Unesp), School of Agricultural and Veterinarian Sciences, Jaboticabal. The individual diaspores biometric analysis was performed by measuring the length, diameter, mass, and weight of a thousand diaspores, the data were subjected to descriptive statistical analysis. It was adopted a completely randomized design in a 5 × 2 factorial with four replications of 25 seeds per treatment. Five temperatures (25; 30; 35; 20-30 and 25-35 °C) and two light regimes (presence and total absence of light) were evaluated. The variables analyzed were germination, germination speed index, the average length of the primary root and shoot, diameter of the stem, and seedlings total dry mass. The length, diameter, and average weight of the diaspores were 12.54 mm, 6.05 mm, and 0.1610 g, respectively. The seeds of Ptychosperma macarthurii germinated in a wide temperature range, reaching a higher germination percentage at 25 °C and a higher germination speed index at 30 °C, being classified as neutral photoblastics. The constant temperature of 30 °C provided higher mean values for all seedlings' biometric characteristics.
Keywords: growth; Heat; palm tree; photoblastia